2020
DOI: 10.1177/2340944420941440
|View full text |Cite
|
Sign up to set email alerts
|

A nonparametric analysis of competitiveness efficiency: The relevance of firm size and the configuration of competitive pillars

Abstract: This study employs a data envelopment analysis (DEA) model with a single constant input to analyze the competitiveness performance of a unique sample of 103 knowledge-intensive business service (KIBS) firms from Hungary, Spain, Colombia, and Costa Rica for the year 2017. Also, we assess how the configuration of competitive pillars—strengths and weaknesses—affects efficiency and how firm size moderates this relationship. The mean efficiency scores by which the competitiveness output can be optimized is 47.43%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
1
15
0
3
Order By: Relevance
“…More recently, Foster and Rosenzweig (2017) proposed a theoretical model that incorporates factor market imperfections and economies of size in mechanization. Their model presents a size-land productivity relationship with a U-shaped pattern, with the highest levels being achieved by the smallest and largest farms, which is in line with the assumption of greater selfexploitation of family labour (Griffin et al 2002) as well https://doi.org/10.17221/384/2021-AGRICECON as with the resource-based theory explaining competitive advantage based on the heterogeneous distribution of resources (Lafuente et al 2020).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…More recently, Foster and Rosenzweig (2017) proposed a theoretical model that incorporates factor market imperfections and economies of size in mechanization. Their model presents a size-land productivity relationship with a U-shaped pattern, with the highest levels being achieved by the smallest and largest farms, which is in line with the assumption of greater selfexploitation of family labour (Griffin et al 2002) as well https://doi.org/10.17221/384/2021-AGRICECON as with the resource-based theory explaining competitive advantage based on the heterogeneous distribution of resources (Lafuente et al 2020).…”
supporting
confidence: 57%
“…According to these studies, the competitive weakness of small farms may be due to their lower likelihood of developing economies of scale, lower innovation potential, and higher technical inefficiency. Lafuente et al (2020) found the reason for competitive weakness to be the inability of small farms to capitalise on competitiveness-enhancing investments. Key (2019) added that some recent technological advances (e.g.…”
mentioning
confidence: 99%
“…Social networks' performance, associated with game boosters' social behaviour, utilises OMSNs, even though they behave adversely or shirk their responsibilities [4,15,36,69]. Meanwhile, trustworthiness becomes crucial to building the relationship between the game booster and the users demanding higher- I had to play the games to boost others' scores illegally It is no big deal to enhance users' levels as no one gets hurt It is online gaming's fault that they were taken advantage of I was only playing games that others required me to do all the time I would have played to increase the game levels; the legitimate ones, anyway Efficiency; Al-Eisawi et al, [82]; Wei et al [30] Expert-level enhancer service quality Boosting organisation efficiency Boosting supply chain efficiency Seller and reseller reaction speed Trustworthiness; Gefen et al [70]; Sirdeshmukh et al [26] OMSNs for online games are honest OMSNs care about expert-level demands OMSNs are not opportunistic OMSNs provide good services OMSNs are predictable OMSNs are trustworthy OMSNs know their market OMSNs; Hsiao [49]; Lafuente et al [72] The number of contracted game cooperations and innovation agreements The time spent game networking compared to that established in the agreement…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…OMSNs accommodate and facilitate game boosters with high individual intelligence to analyse, exploit, and actualise their competencies when given the opportunity. Furthermore, game boosters' intellectual opportunism is closely related to outlets such as OMSNs, so they can obtain abnormal economic values by acting as level enhancers, even though others consider it a violation of fair play [2,14,72]. The authors argue that game boosters realise their intellectual opportunism in OMSNs as inconsistent and unprincipled professionals due to their low integrity when searching for abnormal benefits [11,27,73].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Specific competencies, such as innovativeness and technological capabilities, have become requisites for competing in a “Smart” economy. However, not all firms optimize their competitive efficiency to maximize their potential in the same way, and there is no “one size fits all.” Also, other drivers of competitiveness, such as human capital-based, strategic and market-oriented competencies, are “essentials” that firms must master to optimize their competitive potential (Lafuente et al , 2020). Given the distinct resource limitations and contrasting capability frontiers, the driver that should optimally be focalized is likely to differ from firm to firm (Lafuente et al , 2021).…”
Section: The Entrepreneurship Challenges In Latin America: An Overview Of the Special Issue Manuscriptsmentioning
confidence: 99%